The global prevalence of Trichuris trichiura infection in humans (2010-2023): A systematic review and meta-analysis - Hamed Behniafar; Mahdi Sepidarkish; Mehrdad Jafari Tadi; Soghra Valizadeh; Mostafa Gholamrezaei; Faezeh Hamidi; Hossein Pazoki; Faezeh Alizadeh; Nazanin Kianifard; Morteza Sheikhi Nooshabadi; Kimia Bagheri; Faezeh Hemmati; et al. (Elsevier, 2024)
This systematic review and meta-analysis study aimed to evaluate global Trichuris infection prevalence, assessing progress towards the WHO's 2030 target. We searched international databases from 2010-2023, categorizing data by regions and socio-economic variables using a random-effects model. Analyzing 757 articles covering 7154,842 individuals from 78 countries, the study found a pooled global prevalence of (6.64-7.57%), with the highest rates in the Caribbean (21.72%; 8.90-38.18%) and South-East Asia (20.95; 15.71-26.71%) regions. Southern Africa (9.58; 2.11-21.46%), Latin America (9.58; 2.11-21.46%), and Middle Africa Middle Africa (8.94; 6.31-11.98%) also exhibited high prevalence. Eastern Europe had the lowest prevalence at 0.16% (0.09-0.24). Approximately 513 (480−547) million people worldwide were estimated to harbor Trichuris. Moreover ∼1.5% of people tested worldwide (2010-2023) had a moderate to heavy intensity of infection. The study emphasizes the persistent global health threat of Trichuris infection, urging tailored strategies for effective control and prevention on a global scale.